Positive electrode active material, positive electrode having positive electrode active material, and rechargeable lithium battery including positive electrode having positive electrode active material

CN122992013APending Publication Date: 2026-10-27SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610528122.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-04-14
Filing Date
2026-04-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,增加镍含量存在限制,其可由于多种问题(例如由充电和放电导致的结构劣化、与电解质的表面副反应以及由于颗粒破裂导致的劣化)而产生电池的循环寿命的劣化

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992013A_ABST
    Figure CN122992013A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material, a positive electrode having the positive electrode active material, and a rechargeable lithium battery including the positive electrode having the positive electrode active material. The positive electrode active material according to some embodiments of the present disclosure can include a core in the form of secondary particles and a coating portion. The secondary particles can include a lithium nickel-based composite oxide and a plurality of primary particles that can be agglomerated. The coating portion disposed on a surface of the core includes graphene having a layered structure and a lithium ion-conductive solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to positive electrode active materials, positive electrodes having positive electrode active materials, and rechargeable lithium batteries including positive electrodes having positive electrode active materials. Background Technology

[0002] Portable information devices (such as cellular phones, laptops, or smartphones) and electric vehicles already use rechargeable lithium batteries with high energy density as their power source. Recently, there has been active research into using rechargeable lithium batteries with high energy density as a power source for hybrid or electric vehicles, or as a power storage source.

[0003] To achieve the aforementioned objectives, various positive electrode active materials have been investigated. Among them, lithium nickel-based composite oxides (e.g., lithium nickel manganese cobalt oxide or lithium nickel cobalt aluminum oxide), lithium cobalt oxide, and lithium iron phosphate (lithium iron phosphate)-based compounds have been used as positive electrode active materials. Of these, high-nickel-based positive electrode active materials with approximately 80 mol% or more of nickel content can achieve high energy density. However, increasing the nickel content has limitations, as it can lead to a decline in battery cycle life due to various problems, such as structural degradation caused by charging and discharging, surface side reactions with the electrolyte, and degradation due to particle breakage.

[0004] Therefore, to improve structural stability, attempts are being made to coat the surface of positive electrode active materials with carbon-based materials. However, this coating leads to problems such as degradation of ionic conductivity and cycle life characteristics. Therefore, it is advantageous to develop coating techniques that can stabilize the structure of positive electrode active materials without degrading ionic conductivity and cycle life characteristics. Summary of the Invention

[0005] Provides positive electrode active materials with improved structural stability, suppressed increase in powder resistance and improved ionic conductivity.

[0006] By including the aforementioned positive electrode active material, a positive electrode with improved high-temperature cycle life characteristics and / or a rechargeable lithium battery with improved high-temperature cycle life characteristics can be produced.

[0007] According to some embodiments of this disclosure, the positive electrode active material may include a core in the form of secondary particles and a coating portion (coating). The secondary particles may include lithium nickel-based composite oxides and a plurality of aggregateable primary particles. The coating portion disposed on the surface of the core includes graphene having a layered structure and a lithium-ion conductive solid electrolyte.

[0008] In some implementations, the layered structure may include 2 to 50 layers.

[0009] In some embodiments, the graphene coating may be derived from graphite particles having an average size of less than or equal to about 2.5 μm.

[0010] In some embodiments, the graphite particles may have a ratio I ranging from about 0.15 to about 0.50. D / I G It can be found in the Raman spectrum at approximately 1350 cm⁻¹. -1 Peak intensity I at D At approximately 1580cm -1 Peak intensity I at G .

[0011] In some embodiments, a lithium-ion conductive solid electrolyte can be represented as follows:

[0012] Li 1+x1 R x1 M 2-x1 (PO4)3.

[0013] R can be a metal of Al, B, Sn, Ge, or a combination thereof. M can be Ti, Zr, Hf, or a combination thereof. 0 ≤ x1 < 2.

[0014] In some embodiments, the lithium-ion conductive solid electrolyte may be in the form of particles. The average particle size D of the lithium-ion conductive solid electrolyte particles. 50 It can be approximately 1 nm to approximately 1 μm.

[0015] In some embodiments, the positive electrode active material may include graphene in an amount from about 0.01% to about 5% by weight, based on the total weight of the positive electrode active material.

[0016] In some embodiments, the positive electrode active material may include a lithium-ion conductive solid electrolyte in an amount from about 0.05% to about 6% by weight, based on the total weight of the positive electrode active material.

[0017] In some embodiments, the thickness of the coating portion can be from about 1 nm to about 500 nm.

[0018] In some embodiments, the coating portion includes a first coating portion comprising graphene and a second coating portion comprising a lithium-ion conductive solid electrolyte. The first coating portion may be in the form of a coating layer continuously surrounding the surface of the core. The second coating portion may have a discontinuous island geometry on the surface of the core.

[0019] In some embodiments, the positive electrode active material may further include a grain boundary coating portion on the surface of the primary particles, the grain boundary coating portion comprising a lithium-ion conductive solid electrolyte.

[0020] In some embodiments, the lithium nickel-based composite oxide may be represented by the following:

[0021] Li a3 Ni x3 M 3 y3 M 4 z3 O 2-b3 X b3 .

[0022] 0.9≤a3≤1.2, 0.8≤x3<1, 0<y3≤0.2, 0≤z3≤0.2, 0.9≤x3+y3+z3≤1.1, and 0≤b3≤0.1. M 3 and M 4 may each independently be Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or a combination thereof. X may be F, P, S, or a combination thereof.

[0023] In some embodiments, the lithium nickel-based composite oxide may include an amount of nickel that may be greater than or equal to about 80 mol%, based on 100 mol% of the total metals other than lithium in the lithium nickel-based composite oxide.

[0024] In some embodiments, the average particle diameter D of the core 50 may be from about 8 μm to about 20 μm.

[0025] In some embodiments, the powder resistance of the positive electrode active material may be greater than 85 Ω·cm and less than about 150 Ω·cm.

[0026] A positive electrode according to some embodiments of the present disclosure may include a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector and including the positive electrode active material as described above.

[0027] In some embodiments, the interfacial resistance of the positive electrode may be greater than or equal to about 50 Ω and less than about 150 Ω.

[0028] A rechargeable lithium battery according to some embodiments of the present disclosure may include the positive electrode, a negative electrode, and an electrolyte.

[0029] According to some embodiments, the positive electrode active material includes a coating portion containing both a carbon-based material and a lithium ion conductive solid electrolyte, thereby improving structural stability, suppressing an increase in powder resistance, and simultaneously improving ion conductivity.

[0030] According to some embodiments, by including the above positive electrode active material, the positive electrode and the rechargeable lithium battery may have improved high-temperature cycle life characteristics. Attached Figure Description

[0031] Figures 1 to 4 Schematic diagrams showing some embodiments of rechargeable lithium batteries according to this disclosure.

[0032] Figure 5 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Example 2 according to some embodiments of the present disclosure.

[0033] Figure 6 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Comparative Example 1 according to some embodiments of the present disclosure.

[0034] Figure 7 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Comparative Example 2 according to some embodiments of the present disclosure.

[0035] Figure 8 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Comparative Example 3 according to some embodiments of the present disclosure.

[0036] Figure 9 These are scanning electron microscope images of the surface of the positive electrode active material prepared in Comparative Example 4 according to some embodiments of the present disclosure.

[0037] Figure 10 and 11 The results of SEM-EDS analysis of the surface of the positive electrode active material manufactured in Example 2 according to some embodiments of the present disclosure are shown.

[0038] Figure 12 These are photographs of the cross-section of the positive electrode active material prepared in Example 1, taken using a transmission electron microscope according to some embodiments of this disclosure.

[0039] Figure 13 These are photographs of the cross-section of the positive electrode active material prepared in Example 2, taken using a transmission electron microscope according to some embodiments of this disclosure.

[0040] Figure 14 These are photographs of the cross-section of the positive electrode active material prepared in Comparative Example 1, taken using a transmission electron microscope according to some embodiments of the present disclosure.

[0041] Figure 15 These are photographs taken using a transmission electron microscope of the cross-section of the positive electrode active material prepared in Comparative Example 3, according to some embodiments of the present disclosure.

[0042] Figure 16 These are photographs of the cross-section of the positive electrode active material prepared in Comparative Example 4, taken using a transmission electron microscope according to some embodiments of this disclosure. Detailed Implementation

[0043] Specific embodiments will be described in detail below so that those skilled in the art can readily implement them. However, this disclosure may be embodied in many different forms and is not to be construed as limited to the embodiments set forth herein.

[0044] The terminology used herein is not intended to limit the scope of this disclosure. Unless the context clearly requires otherwise, singular expressions include plural expressions.

[0045] As used herein, “combinations thereof” means mixtures, laminates, complexes, copolymers, alloys, blends and / or reaction products of the constituent elements.

[0046] It should be understood that terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the features, quantities, steps, elements, or combinations thereof embodied, but these terms do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.

[0047] In the accompanying drawings, for clarity, the thickness of layers, films, panels, or regions is exaggerated, and throughout the specification, the same reference numerals denote the same elements. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on said other element, or there may be intermediate elements present. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements present.

[0048] In addition, the term "layer" in this article includes not only the geometry formed on the entire surface when viewed from a plan view, but also the geometry formed on a portion of the surface.

[0049] The average particle size can be measured by methods known to those skilled in the art, such as by a particle size analyzer or by transmission electron microscopy or scanning electron microscopy images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each particle size range, and calculating from the obtained value and / or measurement results. Unless otherwise defined, the average particle size D 50 This can mean the diameter of particles that have a cumulative volume of 50% in the particle size distribution. In other words, unless otherwise defined, the average particle size D is... 50This means the diameter of the particles that constitute 50% of the cumulative volume in the particle size distribution obtained by randomly measuring the size (diameter or length of the major axis) of approximately 20 particles in a scanning electron microscope image. In this paper, the size may vary depending on the particle shape relative to the object being measured. For example, the diameter may be measured for spherical particles, while the length of the major axis may be measured for non-spherical particles.

[0050] In this article, "or" is not interpreted as having an exclusive meaning; for example, "A or B" is interpreted as including A, B, and A+B.

[0051] The term "metal" is interpreted to include common metals, transition metals, and metalloids (semi-metals). As used herein, the term "metalloid" refers to an element that has properties intermediate between those of metals and nonmetals. Examples of metalloids include, but are not limited to, boron (B), silicon (Si), germanium (Ge), arsenic (As), antimony (Sb), and tellurium (Te).

[0052] Positive electrode active material

[0053] Some embodiments provide a positive electrode active material, including: a core in the form of secondary particles, comprising a lithium nickel-based composite oxide and a plurality of aggregated primary particles; and a coating portion disposed on the surface of the core, comprising graphene having a layered structure and comprising a lithium-ion conductive solid electrolyte.

[0054] To achieve high energy density, lithium-nickel-based composite oxide positive electrode active materials with high specific capacity are used. Typically, lithium-nickel-based composite oxides can be used in the form of secondary particles in which multiple primary particles aggregate. Due to the repeated volume expansion of the crystal structure accompanying repeated charging and discharging, the arrangement of the primary particles can become misaligned, for example, the gaps between the primary particles widen. This can cause a large difference between the degree of contraction and expansion of the secondary particles and the degree of contraction and expansion of the positive electrode containing the secondary particles. This leads to structural breakage and destruction of the positive electrode active material and the positive electrode, causing the electrochemical charge transport (transfer) network to break down, resulting in charge imbalance (disequilibrium), increasing the area of ​​side reactions with the electrolyte, and deteriorating the cycle life of the battery.

[0055] To address the aforementioned issues, attempts have been made to coat the surface of lithium-nickel-based composite oxide positive electrode active materials with carbon-based materials. While coating with carbon-based materials improves electronic conductivity and structural stability, a trade-off effect occurs that degrades ionic conductivity and cycle life characteristics.

[0056] Meanwhile, when using lithium-ion conductive solid electrolytes with excellent ionic conductivity, there is an effect of improving ionic conductivity, but the powder resistance can increase, which can cause further deterioration of cycle life characteristics.

[0057] According to some embodiments, the positive electrode active material includes both graphene with a layered structure and a lithium-ion conductive solid electrolyte, thereby improving structural stability, powder resistance, and ionic conductivity compared to a positive electrode active material having only one of these coatings. In particular, by coating with graphene with a layered structure, uniform coating is possible, and a dry method (dry process) can be used for coating, which reduces manufacturing costs. Furthermore, the positive electrode active material can easily exhibit its own conductivity by forming a coating including graphene with a layered structure. The inherent conductivity of the positive electrode active material allows for the manufacture of positive electrodes and / or rechargeable lithium batteries without adding conductive materials or with minimal addition of conductive materials, thereby enabling high capacity and high energy density of the positive electrode and / or rechargeable lithium batteries and improving the high-temperature cycle life characteristics of rechargeable lithium batteries.

[0058] Covered part

[0059] The coating portion may be disposed on a core in the form of secondary particles formed by the aggregation of the aforementioned primary particles, and may include graphene with a layered structure and a lithium-ion conductive solid electrolyte.

[0060] Graphene possesses excellent electrical conductivity, which suppresses the increase in powder resistance (through the coating portion) of the positive electrode active material, and the coating portion exhibits electronic conductivity, thereby improving the electronic conductivity of the positive electrode active material. By using the aforementioned positive electrode active material, the amount of conductive agent added during the manufacture of the positive electrode can be minimized, allowing for a relatively larger amount of the added positive electrode active material, thereby providing a positive electrode capable of achieving high capacity and high energy density. Furthermore, even during dry coating, graphene with a layered structure can be uniformly coated, thereby reducing manufacturing costs.

[0061] There is no particular limitation on the number of layers in the layered structure, but it can be measured as a layered structure having, for example, 2 to 50 atomic layers. The coating portion may include graphene having a layered structure having 5 to 50 layers, 8 to 49 layers, 10 to 48 layers, 13 to 47 layers, 15 to 46 layers, 17 to 46 layers, 18 to 40 layers, 18 to 30 layers, or 18 to 20 layers. The number of layers in the layered structure can be measured by high-resolution transmission electron microscopy (HR-TEM) images of the positive electrode active material particles.

[0062] Interlayer spacing d of layered structure 002The interlayer spacing d of the layered structure can be from about 0.320 nm to about 0.350 nm, for example, from about 0.325 nm to about 0.348 nm, from about 0.328 nm to about 0.345 nm, or from about 0.330 nm to about 0.342 nm. 002 When the above range is met, the conductivity of the positive electrode active material itself can be further improved. Interlayer spacing d 002 The interlayer spacing d of the layered structure can be measured using methods known to those skilled in the art. 002 The peaks on the 002 plane can be obtained via X-ray diffraction (XRD) of the covered portion, and then analyzed. The 002 plane represents the range of 25.0° < 2θ < 27.0°, where 2θ represents the diffraction angle. Standard procedures provided in the XRD apparatus can be used as data processing and analysis procedures, allowing the XRD measurement data to undergo noise removal (i.e., baseline setting). Furthermore, the profiles of the peaks on the 002 plane can be fitted using conventional fitting functions such as Gaussian or Lorentz functions. Additionally, the interlayer spacing d of the layered structure... 002 The interlayer spacing (d) of graphite particles can be measured. 002 The method is used to represent the interlayer spacing d of the graphite particles. 002 It can be measured by XRD analysis of graphite particles.

[0063] The graphene coating may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G When graphene's I D / I G When the value meets the above range, the active material of the positive electrode itself can be given conductivity.

[0064] The graphene coating can be derived from graphite microparticles. The coating can be formed on the surface of the core particle with a uniform thickness, and can impart conductivity to the positive electrode active material powder. "Graphite microparticles" means graphite as microparticles, and "microparticles" means particles with an average particle size or diameter on the order of several nanometers to several micrometers (approximately several nanometers to several micrometers). Specifically, in this disclosure, graphite microparticles are graphite having an average size of less than or equal to about 2.5 μm. By including a coating containing graphite microparticles, even using a small amount of graphite microparticles, the positive electrode active material can also possess electronic conductivity. The graphite microparticles can be commercially available graphite or graphite manufactured from it, provided that the graphite microparticles meet the aforementioned average particle size requirement.

[0065] There are no particular restrictions on the type of graphite particles, as long as they include some form of graphite, and may include, for example, natural or artificial graphite.

[0066] Graphite microparticles may have a plate geometry, and the average size of the graphite microparticles may be less than or equal to about 2 μm, less than or equal to about 1.5 μm, less than or equal to about 1 μm, less than or equal to about 0.7 μm, less than or equal to about 0.5 μm, or less than or equal to about 0.3 μm and may be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, greater than or equal to about 0.07 μm, greater than or equal to about 0.1 μm, or greater than or equal to about 0.2 μm. The average size of the graphite microparticles can be measured by a particle size analyzer and means the size of the particles having a cumulative volume of 50% in the particle size distribution. Furthermore, particle size here may mean the length of the major axis in the plane perpendicular to the thickness direction in the plate geometry. When the average size of the graphite microparticles meets the above ranges, a coating of uniform thickness can be formed on the surface of the core particles, and the positive electrode active material including the coating can exhibit powder conductivity.

[0067] Graphite microparticles may have a density of less than or equal to about 500 nm, for example, about 10 nm to about 500 nm, about 20 nm to about 400 nm, about 30 nm to about 300 nm, about 40 nm to about 200 nm, about 50 nm to about 150 nm, or about 60 nm to about 120 nm. 10 D of graphite particles 10 The particle size distribution of graphite microparticles can be obtained as follows: A particle size analyzer is used to obtain the particle size distribution, and the diameter of the particles representing 10% of the cumulative volume in the particle size distribution is taken as D. 10 Furthermore, grain size here can mean the length of the major axis in the plane perpendicular to the thickness direction in the plate geometry.

[0068] Graphite microparticles may have a density of less than or equal to about 20 μm, for example, about 5 μm to about 20 μm, about 6 μm to about 18 μm, about 7 μm to about 16 μm, about 8 μm to about 14 μm, about 9 μm to about 12 μm, or about 10 μm to about 12 μm. 90 The D of the above-mentioned graphite particles 90 The particle size distribution of graphite microparticles can be obtained as follows: A particle size analyzer is used to obtain the particle size distribution, and the diameter of the particles representing 90% of the cumulative volume in the particle size distribution is taken as D. 90 Furthermore, grain size can refer to the length of the major axis in a plane perpendicular to the thickness direction within the plate geometry.

[0069] The span value of graphite particles can be greater than about 1, for example, about 1.05 to about 8, about 1.1 to about 7, about 1.2 to about 6, or about 1.4 to about 5. The span of graphite particles can be expressed as (D 90 -D 10 ) / D 50 Calculate, and D 10 D 50 and D 90 These values ​​can be taken as diameters corresponding to 10%, 50%, and 90% of the cumulative volume in the particle size distribution, respectively. A larger span value for graphite particles means a wider particle size distribution, while a smaller span value means a narrower and more uniform particle size distribution.

[0070] Graphite particles can have a size of approximately 30 μm. 2 / g to approximately 400 m 2 / g, for example, about 50 m 2 / g to approximately 400 m 2 / g, approximately 100 m 2 / g to approximately 400 m 2 / g, approximately 150 m 2 / g to approximately 400 m 2 / g, approximately 200 m 2 / g to approximately 400 m 2 / g, approximately 250 m 2 / g to approximately 400m 2 / g or approximately 300 m 2 / g to approximately 400 m 2 / g BET specific surface area. The BET specific surface area of ​​graphite particles can be measured using the Brunauer-Emmett-Teller (BET) method. When the BET specific surface area of ​​graphite particles meets the above range, uniform coating is possible, and electronic conductivity can be achieved even with a small amount of coating.

[0071] Graphite microparticles may have a ratio of length of the long axis in the planar direction to thickness of approximately 50 to approximately 1000 in the plate geometry. When the ratio of the length of the long axis in the planar direction to thickness of the graphite microparticles meets the above range, a uniform coating portion can be formed, and the electronic conductivity of the positive electrode active material can be improved. The ratio of the length of the long axis in the planar direction to thickness can be measured based on electron microscopy images. In the scanning electron microscope image of the graphite microparticles, the thickness of the graphite microparticles can be measured, and the length of the long axis in the planar direction orthogonal to the thickness direction can be measured to calculate the ratio. The thickness and the length of the long axis of the graphite microparticles may mean the arithmetic mean of the values ​​obtained through image analysis of multiple graphite microparticles. In addition, the combination of the thickness and the length of the long axis of the graphite microparticles does not necessarily mean that the graphite microparticles are made of the same type of graphite microparticles.

[0072] Graphite microparticles may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G When the I of graphite particles D / I G When the value meets the above range, a coating portion with a uniform thickness can be formed on the surface of the core particle, and the positive electrode active material can maximize the adhesion and conductivity with the electrode plate.

[0073] As described above, in previous studies, while introducing a coating composed solely of carbon-based materials ensured a reduction in powder resistance and an improvement in electronic conductivity, it also resulted in degradation of the ionic conductivity and cycle life characteristics of the lithium-nickel-based composite oxide positive electrode active material. However, according to some embodiments, the coating includes a lithium-ion conductive solid electrolyte and graphene with a layered structure. This achieves the advantages of ensuring structural stability and suppressing the increase in powder resistance through the layered graphene, while simultaneously addressing the disadvantage of degraded ionic conductivity and ensuring ionic conductivity as excellent as when using the lithium-ion conductive solid electrolyte alone.

[0074] Lithium-ion conductive solid electrolytes can be represented by the following chemical formula 1:

[0075] [Chemical Formula 1]

[0076] Li 1+x1 R x1 M 2-x1 (PO4)3.

[0077] In chemical formula 1, R is a metal such as Al, B, Sn, Ge, or a combination thereof. M is a transition metal such as Ti, Zr, Hf, or a combination thereof. Furthermore, 0 ≤ x1 < 2.

[0078] Lithium-ion conductive solid electrolytes can be more specifically represented by the following chemical formula 2:

[0079] [Chemical Formula 2]

[0080] Li 1+x2 Al x2 Ti 2-x2 (PO4)3.

[0081] In chemical formula 2, 0 ≤ x² < 2.

[0082] Lithium-ion conductive solid electrolytes can be in the form of particles with specific geometric shapes (e.g., spherical or ellipsoidal). The average particle size D of lithium-ion conductive solid electrolyte particles... 50 It can be about 1 nm to about 1 μm, for example about 10 nm to about 1 μm, about 50 nm to about 1 μm, about 100 nm to about 1 μm, about 200 nm to about 1 μm, about 200 nm to about 700 nm, about 300 nm to about 700 nm, about 400 nm to about 700 nm, or about 400 nm to about 600 nm. Average particle size D 50 The particle size distribution can be obtained by randomly measuring the dimensions (diameter or length of the major axis) of approximately 20 particles from scanning electron microscope images of lithium-ion conductive solid electrolyte particles. The average particle size is then taken as the diameter of the particles representing 50% of the cumulative volume from this distribution. When the lithium-ion conductive solid electrolyte has a spherical particle shape, the particle size refers to its diameter; when it has a non-spherical particle shape, the particle size refers to the length of its major axis. When the average particle size of the lithium-ion conductive solid electrolyte meets the above range, lithium-ion movement can be facilitated, thereby improving ionic conductivity.

[0083] For example, based on the total weight of the positive electrode active material, the amount may include graphene having a layered structure from about 0.01 wt% to about 5 wt%, such as greater than or equal to about 0.01 wt%, greater than or equal to about 0.02 wt%, greater than or equal to about 0.03 wt%, greater than or equal to about 0.04 wt%, greater than or equal to about 0.05 wt%, greater than or equal to about 0.06 wt%, greater than or equal to about 0.07 wt%, greater than or equal to about 0.08 wt%, greater than or equal to about 0.09 wt%, or greater than or equal to about 0.1 wt% and less than or equal to about 5 wt%, less than or equal to about 4 wt%, less than or equal to about 3 wt%, less than or equal to about 2 wt%, less than or equal to about 1 wt%, less than or equal to about 0.9 wt%, less than or equal to about 0.8 wt%, less than or equal to about 0.7 wt%, less than or equal to about 0.6 wt%, less than or equal to about 0.5 wt%, less than or equal to about 0.4 wt%, less than or equal to about 0.3 wt%, or less than or equal to about 0.2 wt%. When the amount of graphene with a layered structure meets the above range, it can effectively suppress the increase of powder resistance and improve the structural stability of the positive electrode active material.

[0084] Based on the total weight of the positive electrode active material, it can be from about 0.05 wt% to about 6 wt%, for example, greater than or equal to about 0.05 wt%, greater than or equal to about 0.07 wt%, greater than or equal to about 0.09 wt%, greater than or equal to about 0.1 wt%, greater than or equal to about 0.15 wt%, greater than or equal to about 0.2 wt%, greater than or equal to about 0.25 wt%, greater than or equal to about 0.3 wt%, greater than or equal to about 0.35 wt%, greater than or equal to about 0.4 wt%, greater than or equal to about 0.45 wt%, or greater than or equal to about 0.5 wt% and less than or equal to about 6 wt%, less than or equal to about 5 wt%, ... The following amounts comprise lithium-ion conductive solid electrolyte: approximately 4% by weight, less than or equal to approximately 3% by weight, less than or equal to approximately 2% by weight, less than or equal to approximately 1.9% by weight, less than or equal to approximately 1.8% by weight, less than or equal to approximately 1.7% by weight, less than or equal to approximately 1.6% by weight, less than or equal to approximately 1.5% by weight, less than or equal to approximately 1.4% by weight, less than or equal to approximately 1.3% by weight, less than or equal to approximately 1.2% by weight, less than or equal to approximately 1.1% by weight, less than or equal to approximately 1% by weight, less than or equal to approximately 0.9% by weight, less than or equal to approximately 0.8% by weight, less than or equal to approximately 0.7% by weight, or less than or equal to approximately 0.6% by weight. When the amount of lithium-ion conductive solid electrolyte meets the above range, ionic conductivity can be improved without excessively increasing powder resistance, and the structural stability of the positive electrode active material can be improved. If lithium-ion conductive solid electrolyte is included in amounts exceeding the above range, powder resistance may be excessively increased.

[0085] The weight ratio B of the lithium-ion conductive solid electrolyte to the weight A of the layered graphene, B / A, can be from about 1 to about 20, for example from about 1.3 to about 18, from about 1.5 to about 15, from about 1.7 to about 12, from about 1.9 to about 10, or from about 2 to about 8. When the weight ratio B / A of the lithium-ion conductive solid electrolyte to the weight A of the layered graphene satisfies the above range, structural stability can be ensured, the increase in powder resistance can be suppressed, and ionic conductivity can be improved at the same time. In addition, the positive electrode including the positive electrode active material and the rechargeable lithium battery can have improved cycle life characteristics.

[0086] The coating may exist continuously on the core surface or discontinuously.

[0087] The layered graphene and lithium-ion conductive solid electrolyte included in the coating can exist in a mixed state, and can be in the form of a coating layer that exists continuously on the core surface or in the form of islands that exist discontinuously.

[0088] Alternatively, the layered graphene and the lithium-ion conductive solid electrolyte may not exist in a mixed state within the coating portion, but may form separate (separate) coating portions. The coating portion may include a first coating portion and a second coating portion, the first coating portion comprising the layered graphene and the second coating portion comprising the lithium-ion conductive solid electrolyte. The first coating portion may be in the form of a continuous coating layer on the surface of the core, and the second coating portion may be in the form of discontinuous islands on the surface of the core. The geometry of the coating portion can be confirmed by SEM-EDS (energy-dispersive X-ray spectroscopy) elemental mapping analysis of the positive electrode active material, based on the distribution regions of carbon (C) elements included in the layered graphene and phosphorus (P) elements included in the lithium-ion conductive solid electrolyte.

[0089] The first coating portion can conformally coat the surface of a core in the form of secondary particles from which primary particles agglomerate, and the second coating portion can be disposed on the surface of the core, simultaneously disposed on the first coating portion. That is, the second coating portion can be disposed on the first coating portion located at the interface of the primary particles present on the core surface in the conformal surface of the first coating portion.

[0090] In some embodiments, the second covering portion may be disposed on the surface of the core, while simultaneously being disposed above the first covering portion. When the first covering portion is formed to thinly and uniformly cover only a portion of the core surface rather than the entire core surface, the second covering portion may be formed on the surface of the core not covered by the first covering portion. The second covering portion may be formed not only on the surface of the core not covered by the first covering portion, but also on the first covering portion.

[0091] The geometry of the coating portion can be adjusted by changing the method of forming the coating portion on the positive electrode active material. When graphite microparticles and a lithium-ion conductive solid electrolyte are mixed together and then coated onto a core of the positive electrode active material, the coating portion can be formed as a continuous or discontinuous coating portion on the surface of the core, while the layered graphene and the lithium-ion conductive solid electrolyte are mixed with each other. Alternatively, if the graphite microparticles and the lithium-ion conductive solid electrolyte are not mixed and are coated onto the core separately, the first and second coating portions can exist on the core in various forms, depending on which of the two materials is coated first and how much of each material is used. Various coating methods can be used, or can be adjusted or modified using various methods known to those skilled in the art to which this disclosure pertains.

[0092] When the coating portion has the form of a coating layer continuously existing on the surface of the core, the coating portion can be formed very thinly and uniformly, and the thickness of the coating portion can be from about 1 nm to about 500 nm, for example, from about 10 nm to about 450 nm, from about 10 nm to about 400 nm, from about 10 nm to about 350 nm, from about 10 nm to about 300 nm, from about 10 nm to about 250 nm, from about 10 nm to about 200 nm, from about 10 nm to about 150 nm, from about 10 nm to about 100 nm, from about 10 nm to about 80 nm, or from about 10 nm to about 50 nm. When the thickness of the coating portion meets the above ranges, the structural stability of the positive electrode active material is improved, the increase in powder resistance is suppressed, and the ionic conductivity is improved at the same time. In addition, the high-temperature cycle life characteristics of the positive electrode including it and the rechargeable lithium battery can be improved. The thickness of the coating can be measured, for example, by TEM images of the cross-section of the positive electrode active material, or by TOF-SIMS analysis (surface analysis via time-of-flight secondary ion mass spectrometry), XPS analysis (X-ray photoelectron spectroscopy), or EDS analysis (energy-dispersive X-ray spectroscopy). The thickness of the coating can mean the sum of the thicknesses of the first coating and the second coating.

[0093] Simultaneously, the positive electrode active material may further include a grain boundary coating portion, which is disposed on the surface of the primary particles inside the core and includes a lithium-ion conductive solid electrolyte. The grain boundary coating portion may exist within the internal portion of the secondary particles (i.e., not on the surface) and may coat along the interface of the primary particles present in the internal portion of the secondary particles. The internal portion of the secondary particles means the entire internal portion (i.e., the core) excluding the surface of the secondary particles, and for example, the internal portion of the secondary particles may mean the entire internal portion from a depth of approximately 2 μm from the core surface, and may also mean the portion not contacted by distilled water when washing the secondary particles of the positive electrode active material with distilled water. The grain boundary coating portion may further include graphene with a layered structure along with the lithium-ion conductive solid electrolyte.

[0094] There are no particular limitations on the method of forming the coating portion, which includes graphene with a layered structure and a lithium-ion conductive solid electrolyte, but it can be, for example, dry mixing (dry blending).

[0095] Dry mixing can include methods in which a core comprising a plurality of primary particles agglomerated from lithium nickel-based composite oxides, graphite microparticles as a coating material, and a lithium-ion conductive solid electrolyte are mixed to form a coating portion by applying mechanical energy without the use of a solvent. “Dry” can mean a state in which there is no intentional contact with a solvent, such as a process solvent, or it can mean a state in which a solvent is not intentionally included.

[0096] Dry mixing methods may include, but are not limited to: a) a method in which a coating material, such as graphite microparticles and a lithium-ion conductive solid electrolyte, is brought into contact with a core surface using, for example, a low-rotation ball mill, such that the graphite microparticles and lithium-ion conductive solid electrolyte, as coating materials, adhere to the surface of the core particles, and simultaneously, the adhered coating material particles agglomerate to form a coating portion; b) a method in which the coating material is confined to the core surface by the movement of a grinding medium or by a rotor within the apparatus, such that the core and the coating material are combined, and simultaneously, the coating material on the core is mechanically combined to each other by stress accompanying the coating material, or the coating material on the core is combined by thermal softening or melting caused by stress; c) a method in which the core with the coating portion formed by a) and / or b) above is heat-treated, such that part or all of the coating portion and the core melts, and then cooled again. However, this disclosure is not limited to these methods, and any dry method applicable in the relevant art can be used.

[0097] Dry mixing can be performed using ball milling methods such as planetary ball milling, low-speed ball milling, high-speed ball milling, or mechanical fusion. For example, a dry method can be performed using mechanical fusion. Mechanical fusion is a method in which the mixture is placed in a rotating container, the mixture is fixed to the inner wall of the container by centrifugal force, and then the mixture is compressed through the gap between the inner wall of the container and an arm head slightly close to the inner wall. Mechanical fusion corresponds to method b) above. The container can be, for example, a mixer with blades inside, and the mixer can have a diameter of about 5 cm to about 15 cm and a gap of about 0.01 mm to about 0.1 mm. There is no particular limitation on the speed of the mixer, but it can be, for example, about 1,000 rpm to about 5,000 rpm, about 1,500 rpm to about 4,500 rpm, about 2,000 rpm to about 4,000 rpm, or about 2,500 rpm to about 3,500 rpm, and the rotation time can vary depending on the speed, but can be about 30 seconds to about 1 hour, about 1 minute to about 30 minutes, or about 5 minutes to about 15 minutes.

[0098] Prior to dry mixing, the process may further include preparing the core, graphite microparticles, and lithium-ion conductive solid electrolyte. Since the layered graphene included in the coating portion can be derived from the graphite microparticles described above, the graphite microparticles can be prepared as the coating material. The graphite microparticles and lithium-ion conductive solid electrolyte can be described in the same manner as the graphite microparticles and lithium-ion conductive solid electrolyte of the coating portion described above, and therefore, their detailed description will be omitted. Since the core can be described in the same manner as the core described later, its detailed explanation will also be omitted.

[0099] Graphite microparticles can be obtained from commercially available sources or can be prepared by pulverizing graphite.

[0100] There are no particular restrictions on the type of graphite, and it can be, for example, flake graphite. Graphite can be the same type used in rechargeable lithium batteries.

[0101] Flake graphite can have an average size of about 3 μm to about 25 μm, for example, about 3 μm to about 20 μm, about 3 μm to about 15 μm, about 3 μm to about 10 μm, about 3 μm to about 8 μm, about 3 μm to about 6 μm, about 3 μm to about 4 μm, or about 3 μm to about 3.5 μm. The average size of flake graphite means the size of particles having a cumulative volume of 50% in the particle size distribution. Furthermore, flake graphite can have a plate-like particle shape, and the particle size can mean the length of the major axis in the plane perpendicular to the thickness direction in the plate geometry. The average size of flake graphite can be measured from scanning electron microscopy images. Additionally, the average size of flake graphite can be measured using a particle size analyzer.

[0102] Flake graphite may have a Raman spectral density of about 0.01 to about 0.15, for example about 0.02 to about 0.14, about 0.08 to about 0.14, or about 0.1 to about 0.14 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .

[0103] Grinding processes can be used for pulverization. Grinding processes can utilize methods known to those skilled in the art, and for example, devices such as ball mills, bead mills, spray mills, pin mills, roller mills, or air classifiers (ACMs) can be used.

[0104] A ball mill can be used for pulverization, and zirconia beads (ZrO2 beads) with a size of about 1 mm to about 3 mm can be used as the pulverizing medium. The size of the zirconia beads can be about 1.2 mm to about 2.8 mm, about 1.3 mm to about 2.7 mm, or about 1.5 mm to about 2.5 mm. If the size of the balls meets the above range, the particle size of the graphite particles can be controlled to the desired level.

[0105] When using a ball mill for pulverization, there is no particular limitation on the number of balls to be introduced, but for example, balls can be introduced in amounts from about 500 parts by weight to about 2000 parts by weight of graphite per 100 parts by weight. Based on 100 parts by weight of graphite, balls can be added in amounts from about 600 parts by weight to about 1800 parts by weight, from about 700 parts by weight to about 1600 parts by weight, from about 800 parts by weight to about 1400 parts by weight, or from about 900 parts by weight to about 1100 parts by weight.

[0106] The grinding process can vary depending on the grinding apparatus and is not particularly limited. However, when using a ball mill, it can be carried out at speeds of approximately 200 rpm to approximately 5000 rpm, for example, approximately 250 rpm to approximately 4500 rpm, approximately 300 rpm to approximately 4000 rpm, approximately 400 rpm to approximately 3000 rpm, or approximately 600 rpm to approximately 3000 rpm. The grinding time can vary depending on the grinding speed and is not particularly limited, but can be approximately 30 minutes to approximately 3 hours or approximately 35 minutes to approximately 3 hours. When the grinding speed and time meet the above ranges, the particle size of the graphite microparticles can be controlled to the desired level.

[0107] Graphite microparticles are prepared by pulverizing graphite according to the above-described pulverization method. Therefore, the graphite microparticles can possess excellent electronic conductivity, and simultaneously, by pulverizing graphite microparticles with a dense structure, the specific surface area can be increased.

[0108] core

[0109] The core of the positive electrode active material includes a lithium-nickel based composite oxide. The core can achieve high capacity and high energy density by comprising the lithium-nickel based composite oxide.

[0110] The lithium-nickel based composite oxide may be represented by the following Chemical Formula 3:

[0111] [Chemical Formula 3]

[0112] Li a3 Ni x3 M 3 y3 M 4 z3 O 2-b3 X b3 .

[0113] In Chemical Formula 3, 0.9≤a3≤1.2, 0.8≤x3<1, 0<y3≤0.2, 0≤z3≤0.2, 0.9≤x3+y3+z3≤1.1, and 0≤b3≤0.1. Furthermore, M 3 and M 4 are each independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or a combination thereof. Still further, X is F, P, S, or a combination thereof.

[0114] In Chemical Formula 3, 0.85≤x3<1, 0<y3≤0.15, and 0≤z3≤0.15; or 0.9≤x3<1, 0<y3≤0.1, and 0≤z3≤0.1.

[0115] The lithium-nickel based composite oxide may, for example, be independently represented by Chemical Formula 4 or Chemical Formula 5.

[0116] Chemical Formula 4 is as follows:

[0117] [Chemical Formula 4]

[0118] Li a4 Ni x4 Co y4 M 5 z4 O 2-b4 X b4 .

[0119] In Chemical Formula 4, 0.9≤a4≤1.2, 0.8≤x4<1, 0<y4≤0.2, 0≤z4≤0.2, 0.9≤x4+y4+z4≤1.1, and 0≤b4≤0.1. Furthermore, M 5X is Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or combinations thereof. Furthermore, X is F, P, S, or combinations thereof.

[0120] In chemical formula 4, 0.9≤x4≤0.99, 0.01≤y4≤0.1, and 0≤z4≤0.1.

[0121] Chemical formula 5 is as follows:

[0122] [Chemical Formula 5]

[0123] Li a5 Ni x5 Co y5 M 6 z5 M 7 w5 O 2-b5 X b5 .

[0124] In chemical formula 5, 0.9 ≤ a5 ≤ 1.2, 0.8 ≤ x5 ≤ 0.98, 0.01 ≤ y5 ≤ 0.19, 0.01 ≤ z5 ≤ 0.19, 0 ≤ w5 ≤ 0.19, 0.9 ≤ x5 + y5 + z5 + w5 ≤ 1.1, and 0 ≤ b5 ≤ 0.1, M 6 It is Al, Mn, or a combination thereof. Furthermore, M... 7 X is B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr, or combinations thereof. Furthermore, X is F, P, S, or combinations thereof.

[0125] In chemical formula 5, 0.9≤x5≤0.98, 0.01≤y5≤0.09, 0.01≤z5≤0.09, and 0≤w5≤0.09.

[0126] Lithium-nickel-based composite oxides can each be independently used as high-nickel-based positive electrode active materials. These composite oxides can have an amount of nickel greater than or equal to about 80 mol%, for example, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%, based on 100 mol% of total metals excluding lithium. When the amount of nickel meets these ranges, high capacity and high energy density can be achieved.

[0127] The core is a secondary particle formed by the aggregation of multiple primary particles. The secondary particles can be spherical, ellipsoidal, or polyhedral, or can have irregular geometric shapes, while the primary particles can have spherical, ellipsoidal, plate-like, or combinations thereof geometric shapes. The average particle size D of the secondary particles... 50(i.e., the average particle size D of the core) 50 The particle size can be from about 8 μm to about 20 μm, for example, from about 9 μm to about 18 μm, or from about 10 μm to about 15 μm. Average particle size D 50 The particle size distribution can be obtained by randomly measuring the dimensions (diameter or length of the major axis) of approximately 20 particles from scanning electron microscope images of lithium-nickel-based composite oxide particles in the form of secondary particles. The diameter of the particles representing 50% of the cumulative volume from this distribution is taken as the average particle size. When the core (i.e., the secondary particle) has a spherical particle shape, the particle size can refer to its diameter; when the core (i.e., the secondary particle) has a non-spherical particle shape, the particle size can refer to the length of its major axis. The average particle size D of the primary particles forming the secondary particles is also considered. 50 The size can be less than or equal to about 6 μm, and can be, for example, about 100 nm to about 4 μm, about 100 nm to about 2 μm, about 200 nm to about 800 nm, or about 300 nm to about 700 nm. The average particle size of the primary particles can be obtained by randomly measuring the size (diameter or length of the major axis) of about 20 primary particles from scanning electron microscopy or transmission electron microscopy images of the surface of the secondary particles to obtain a particle size distribution, and taking the size of the particles with a cumulative volume of 50% of the particle size distribution. When the primary particles forming the secondary particles have a spherical particle shape, the particle size can refer to their diameter, and when the primary particles forming the secondary particles have a non-spherical particle shape, the particle size can refer to the length of their major axis.

[0128] The positive electrode active material can achieve a low powder resistivity by including the aforementioned core and coating portion. The powder resistivity of the positive electrode active material can be greater than about 85 Ω·cm and less than about 150 Ω·cm, for example, greater than about 85 Ω·cm and less than or equal to about 140 Ω·cm, greater than about 85 Ω·cm and less than or equal to about 130 Ω·cm, greater than about 85 Ω·cm and less than or equal to about 120 Ω·cm, greater than about 85 Ω·cm and less than or equal to about 110 Ω·cm, greater than about 85 Ω·cm and less than or equal to about 100 Ω·cm, or greater than about 85 Ω·cm and less than or equal to about 90 Ω·cm. The powder resistivity of the positive electrode active material can be measured by controlling the pressure applied to the powder using a powder resistivity measuring device equipped with a 4-pin probe (i.e., a device such as the product name "RM3543" from the manufacturer "Hioki").

[0129] positive electrode

[0130] Some embodiments provide a positive electrode, which includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector and including the aforementioned positive electrode active material.

[0131] By incorporating the aforementioned positive electrode active material, the positive electrode can possess a relatively low interfacial resistance. The interfacial resistance of the positive electrode can be greater than or equal to about 50 Ω and less than about 150 Ω, for example, about 60 Ω to about 140 Ω, about 70 Ω to about 130 Ω, about 80 Ω to about 120 Ω, about 90 Ω to about 110 Ω, or about 100 Ω to about 110 Ω. The interfacial resistance of the positive electrode can be measured using an electrochemical impedance spectroscopy (EIS), and for example, the amplitude can be ±10 mV and the frequency range can be about 10 mHz to about 1 MHz. The measurement of the interfacial resistance of the positive electrode can be performed by charging the battery to a maximum voltage of 4.25 V based on the Li negative electrode at a constant current of 0.1C, then cutting off the current at a 0.05C rate while maintaining a constant voltage of 4.25 V, and allowing it to stand for a 1-hour pause. Then, the interface resistance of the positive electrode can be measured using an impedance analyzer under balanced voltage conditions according to the 2-probe method.

[0132] Positive electrode current collector

[0133] There are no particular restrictions on the positive electrode current collector, as long as it is conductive and does not cause chemical changes in the rechargeable lithium battery. The positive electrode current collector can be an aluminum foil or stainless steel foil with a thickness of about 10 μm to about 15 μm.

[0134] Positive electrode active material layer

[0135] The positive electrode active material layer includes the aforementioned positive electrode active material.

[0136] The details of the positive electrode active material are the same as those described above, and therefore, descriptions of those details are omitted below.

[0137] The amount of positive electrode active material can be from about 60% to about 99.9% by weight, from about 70% to about 99.8% by weight, from about 80% to about 99% by weight, or from about 90% to about 98% by weight, based on the total weight of the positive electrode active material layer. When the aforementioned positive electrode active material is included, the same effect can be achieved using relatively less conductive material compared to using known positive electrode active materials, and therefore, a relatively large amount of positive electrode active material can be included. Therefore, energy density can be improved.

[0138] The positive electrode active material layer may optionally further include a binder, a conductive material, or a combination thereof.

[0139] The binder improves the adhesion between the active material particles of the positive electrode and to the positive electrode current collector. Examples of binders may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers (polymers containing ethylene oxide), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin and / or nylon, but the binder is not limited to these.

[0140] Conductive materials are included to provide electrode conductivity, and any electrically conductive material may be used as a conductive material unless it causes a chemical change. Examples of conductive materials may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers and / or carbon nanotubes; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum and / or silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0141] In the positive electrode active material layer, the amount of binder can be from about 0.1 wt% to about 5 wt% based on the total weight of the positive electrode active material layer, and the amount of conductive material can be from about 0.1 wt% to about 5 wt% based on the total weight of the positive electrode active material layer.

[0142] In addition to the aforementioned components, the positive electrode active material layer may further include irreversible positive electrode additives to the extent that it does not impair the purpose of the present invention.

[0143] Irreversible positive electrode additives are compounds that act as sacrificial positive electrodes, compensating for the irreversible conversion of Li that no longer participates in the charging / discharging reaction by participating in the formation of an SEI (solid electrolyte interphase) film on the surface of the negative electrode during charging / discharging. Irreversible positive electrode additives are compounds that decompose during the formation process to provide Li and do not participate in subsequent charging / discharging processes. By adding such irreversible positive electrode additives, consumed lithium can be replenished, thereby compensating for lithium loss and improving the battery's energy density, cycle life, and stability.

[0144] Irreversible positive electrode additives include compounds used as sacrificial positive electrodes, such as Fe-containing oxides, Mn-containing oxides, and Co-containing oxides.

[0145] The Fe-containing oxides may include Li5FeO4, LiFeO2, LiFe5O8, or combinations thereof. The Mn-containing oxides may include overlithiated manganese oxides, with an example of an overlithiated manganese oxide being Li6MnO4. The Co-containing oxides may include overlithiated cobalt oxides, with an example of an overlithiated cobalt oxide being Li6CoO4.

[0146] Rechargeable lithium batteries

[0147] A rechargeable lithium battery according to some embodiments includes the above-described positive electrode, negative electrode, and electrolyte. A rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte.

[0148] Depending on the geometry of the rechargeable lithium battery, rechargeable lithium batteries can be classified as cylindrical, prismatic, pouch-shaped, or coin-shaped.

[0149] Figures 1 to 4 Schematic diagrams showing some embodiments of rechargeable lithium batteries according to this disclosure. Figure 1 Displays a cylindrical battery. Figure 2 Displays a prismatic battery, and Figure 3 and 4 Each battery is shown with a pouch geometry. The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 between a positive electrode 10 and a negative electrode 20, and the electrode assembly 40 is housed within the housing 50. The positive electrode 10, negative electrode 20, and separator 30 may be impregnated with an electrolyte (not shown). The rechargeable lithium battery 100 may include a seal 60 for sealing the housing 50, such as... Figure 1 As shown. Additionally, in Figure 2 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and 4 As shown, the rechargeable lithium battery 100 includes electrode terminals 70, namely, positive electrode terminal 71 and negative electrode terminal 72, which serve as electrical paths for leading current formed in the electrode assembly 40 to the outside.

[0150] Because some details regarding the positive electrode included in the rechargeable lithium battery are the same as those described above, those details are omitted below. The rechargeable lithium battery according to embodiments of this disclosure, by including the aforementioned positive electrode, ensures excellent cycle life characteristics and rate performance, while significantly improving electrode resistance.

[0151] negative electrode

[0152] The negative electrode for a rechargeable lithium battery includes a negative electrode current collector and a layer of negative electrode active material on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and may optionally further include a binder, a conductive material, or a combination thereof.

[0153] The negative electrode current collector is not particularly limited as long as it has electrical conductivity and does not cause chemical changes in a rechargeable lithium battery, and may be a copper foil having a thickness of about 10 μm to about 15 μm.

[0154] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.

[0155] The material capable of reversibly intercalating / deintercalating lithium ions may include a carbon-based negative electrode active material, for example, crystalline carbon, amorphous carbon, or a combination thereof. The crystalline carbon may be irregular, or flake, scaly, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, a mesophase pitch carbonized product, or calcined coke.

[0156] As the alloy of lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.

[0157] The material capable of doping and dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may be silicon, a silicon-carbon composite, SiO x (0<x≤2), a Si-Q alloy (wherein Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements [excluding Si], Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and for example, selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO₂, a Sn alloy, or a combination thereof.

[0158] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle diameter D of the silicon-carbon composite particles 50 may be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. The silicon-carbon composite may include secondary particles (core) in which silicon primary particles are aggregated and an amorphous carbon coating layer (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the silicon primary particles, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0159] The silicon-carbon composite may further include crystalline carbon. The silicon-carbon composite may include a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon or hard carbon, a mesophase pitch carbonized product, or calcined coke.

[0160] When the silicon-carbon composite includes silicon and amorphous carbon, based on the total weight of the silicon-carbon composite, the amount of silicon may be about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be about 50 wt% to about 90 wt%. In addition, when the composite includes silicon, amorphous carbon, and crystalline carbon, based on the total weight of the silicon-carbon composite, the amount of silicon may be about 10 wt% to about 50 wt%, the amount of crystalline carbon may be about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be about 20 wt% to about 40 wt%.

[0161] In addition, the thickness of the amorphous carbon coating layer may be about 5 nm to about 100 nm. The average particle diameter D of the silicon particles (primary particles) 50 may be about 10 nm to about 1 μm, or about 10 nm to about 200 nm. The silicon particles may exist as elemental silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented by SiO x (0<x≤2). The Si:O atomic ratio representing the oxidation degree may be about 99:1 to about 33:67. As used herein, unless otherwise defined, the average particle diameter D 50 refers to the diameter of particles at a cumulative volume of about 50 vol% in the particle size distribution.

[0162] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When a mixture of the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material is used, the mixing ratio by weight may be about 1:99 to about 90:10.

[0163] Based on the total weight of the negative electrode active material layer, the negative electrode active material may be included in an amount of about 90 wt% to about 99.8 wt%, or about 94 wt% to about 99 wt%.

[0164] The binder serves to well adhere the negative electrode active material particles to each other, and also serves to adhere the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0165] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or a combination thereof.

[0166] Waterborne adhesives may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxygenated alcohol, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or combinations thereof.

[0167] When an aqueous binder is used as the negative electrode binder, it may further include a cellulose-based compound capable of imparting viscosity. As a cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts may be mixed and used. The alkali metal may be Na, K, or Li.

[0168] Dry adhesives can be polymeric materials that can be turned into fibers and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0169] Conductive materials are included to provide electrode conductivity, and any electrically conductive material may be used as a conductive material unless it causes a chemical change. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers and / or carbon nanotubes; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum and / or silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0170] Based on the total weight of the negative electrode active material layer, the amount of binder can be from about 0.1% to about 5% by weight, and based on the total weight of the negative electrode active material layer, the amount of conductive material can be from about 0.1% to about 5% by weight.

[0171] electrolytes

[0172] The electrolyte used in rechargeable lithium batteries may be an electrolyte solution, which may include non-aqueous organic solvents and lithium salts.

[0173] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of a battery. Non-aqueous organic solvents can be carbonate (carbonate-based) solvents, ester (ester-based) solvents, ether (ether-based) solvents, ketone (ketone-based) solvents, alcohol (alcohol-based) solvents, aprotic solvents, or combinations thereof.

[0174] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and / or butyl carbonate (BC). Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanolactone, mevalonolactone, valproic acid lactone, and / or caprolactone. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and / or tetrahydrofuran. Additionally, ketone solvents may include cyclohexanone. Alcohol solvents may include ethanol and / or isopropanol, and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings or ether groups); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane and / or 1,4-dioxolane; and / or sulfolane.

[0175] Non-aqueous organic solvents can be used alone or in mixtures of two or more types, and when two or more types are used in mixtures, the mixing ratio can be appropriately adjusted according to the desired battery performance, as is widely known to those skilled in the art.

[0176] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.

[0177] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. Carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.

[0178] The electrolyte solution may further include vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve the cycle life of the battery.

[0179] Examples of ethylene carbonate compounds may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0180] Lithium salts dissolved in non-aqueous organic solvents supply lithium ions in the battery, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include at least one selected from: LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0181] The concentration of lithium salt can be in the range of about 0.1 M to about 2.0 M. When the concentration of lithium salt is within the above range, the electrolyte solution has appropriate ionic conductivity and viscosity, which allows the battery to operate well and allows lithium ions to move efficiently.

[0182] diaphragm

[0183] Depending on the type of rechargeable lithium battery, a separator may be present between the positive and negative electrodes. The separator may comprise a multilayer membrane of polyethylene, polypropylene, polyvinylidene fluoride, or two or more layers, and / or may comprise a hybrid multilayer membrane such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, and / or a polypropylene / polypropylene / polypropylene three-layer separator.

[0184] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.

[0185] The porous substrate may be a polymer film formed from any of the following polymers: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene ether; cyclic olefin copolymer; polyphenylene sulfide; polyethylene naphthalate; and polytetrafluoroethylene (e.g., Teflon). ® (TEFLON ® The porous substrate can be formed of glass fiber, or it can be a membrane in which polymer and glass fiber are mixed.

[0186] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.

[0187] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit derived from (meth)acrylamide, the second structural unit including at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylaminosulfonic acid or a salt thereof.

[0188] Inorganic materials may include inorganic particles selected from the following: Al₂O₃, SiO₂, TiO₂, SnO₂, CeO₂, MgO, NiO, CaO, GaO, ZnO, ZrO₂, Y₂O₃, SrTiO₃, BaTiO₃, Mg(OH)₂, boehmite, or combinations thereof, but are not limited to these. The average particle size D of the inorganic particles... 50 It can be about 1 nm to about 2000 nm, for example about 100 nm to about 1000 nm or about 100 nm to about 700 nm.

[0189] Organic and inorganic materials can be mixed in a coating, or coatings containing organic materials and coatings containing inorganic materials can be stacked.

[0190] The coating thickness can be from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm or from about 1 μm to about 5 μm.

[0191] The present invention will now be described in detail through embodiments. However, the embodiments described below are merely examples for illustrating implementation of the present disclosure, and the present disclosure is not limited to the embodiments described below.

[0192] Example 1

[0193] (1) Preparation of positive electrode active material

[0194] Nickel-based hydroxide precursors (Ni) were prepared as follows: 0.91 Co 0.08 Al 0.01 (OH)2): Nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O) and sodium aluminum sulfate (NaAl(SO4)2·12H2O) are added to distilled water in a molar ratio of 91:8:1. Then, ammonia water (NH4OH) is added as a complexing agent and stirred for 18 hours to carry out a coprecipitation reaction.

[0195] A nickel-based hydroxide precursor was mixed with LiOH to achieve a molar ratio of Li:(Ni+Co+Al) of 1:1, and the mixture was calcined at 730°C for 8 hours in an oxygen atmosphere to prepare core particles.

[0196] The core particles are secondary particles formed by the aggregation of primary particles, and the secondary particles have an average particle size of approximately 16 μm (D). 50 And possesses lithium-nickel based composite oxide (LiNi) 0.91 Co 0.08 Al 0.01 The composition of O2.

[0197] Furthermore, 4 g of flake graphite (product name: G5, manufacturer: C-one; average size 3 μm, and Raman spectra at 1350 cm⁻¹) was used. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G 0.12 g of ZrO2 beads with a particle size of 2 mm were mixed with 40 g of ZrO2 beads. Subsequently, the flake graphite was milled at 1,000 rpm for 1 hour to prepare graphite microparticles.

[0198] The core particles and graphite microparticles (average size 0.26 μm, BET specific surface area 300 m²) were used. 2 / g, and in the Raman spectrum at 1350cm -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G (0.28) and an average particle size D of 0.5 μm 50 Li 1.3 Al 0.3 Ti 1.7 The lithium-ion conductive solid electrolyte of (PO4)3 (product name: L0409, manufacturer: Sejin C&I) was placed in a dry mixer and then dry-mixed by applying a shear rate of 1000 rpm for 1 minute to prepare the positive electrode active material, wherein a coating portion containing graphene with a layered structure derived from graphite microparticles and lithium-ion conductive solid electrolyte was formed on the surface of the core particles.

[0199] Based on the total weight of the positive electrode active material, it includes 0.1% by weight of graphene with a layered structure and 0.5% by weight of lithium-ion conductive solid electrolyte.

[0200] (2) Manufacturing of the positive electrode

[0201] The prepared positive electrode active material, polyvinylidene fluoride as a binder, and carbon black as a conductive material were mixed in a weight ratio of 96:2:2. The mixture was then added to and dispersed in an N-methyl-2-pyrrolidone solvent to prepare a slurry for forming the positive electrode active material layer. The slurry was coated onto an aluminum foil, then compressed and dried to manufacture the positive electrode.

[0202] (3) Manufacturing of rechargeable lithium battery cells

[0203] A 2032-type coin cell was fabricated using a manufactured positive electrode and a lithium metal counter electrode (i.e., operating as a negative electrode). A separator made of porous polyethylene membrane with a thickness of approximately 16 μm was placed between the positive electrode and the lithium metal counter electrode, and an electrolyte solution was injected into the assembly of the separator, positive electrode, and lithium metal counter electrode. The electrolyte solution was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:5 and dissolving 1.1 M LiPF6 in the mixed solvent.

[0204] Example 2

[0205] The same core particles, graphite microparticles, and lithium-ion conductive solid electrolyte as in Example 1 were prepared in the same amounts as in Example 1, but the graphite microparticles and lithium-ion conductive solid electrolyte were coated onto the core particles using a different coating method to prepare the positive electrode active material.

[0206] Specifically, core particles and graphite microparticles are placed in a dry mixer and then dry-mixed for 10 minutes by applying a shear force of 1000 rpm to the core particles and graphite microparticles to form a first coating portion on the core particles, comprising a layered graphene structure derived from the graphite microparticles. Subsequently, a lithium-ion conductive solid electrolyte is added to the core particles on which the first coating portion has been formed, and then the mixture is ball-milled again for 30 minutes to further form a second coating portion comprising the lithium-ion conductive solid electrolyte on the core particles on which the first coating portion has been formed, thereby preparing the positive electrode active material.

[0207] Except that the prepared positive electrode active material is used instead of the positive electrode active material of Example 1, the positive electrode and the rechargeable lithium battery cell including the positive electrode are manufactured in the same manner as in Example 1.

[0208] Comparative Example 1

[0209] The positive electrode active material was prepared in essentially the same manner as in Example 1, except that in “(1) Preparation of positive electrode active material” in Example 1, the core particles and graphite microparticles were dry-mixed separately without the addition of lithium-ion conductive solid electrolyte, and then the positive electrode active material was used to manufacture the positive electrode and rechargeable lithium battery cell in the same manner as in Example 1.

[0210] Comparative Example 2

[0211] The positive electrode active material was prepared in essentially the same manner as in Example 1, except that in “(1) Preparation of positive electrode active material” in Example 1, the core particles and lithium-ion conductive solid electrolyte were dry-mixed separately without the addition of graphite particles, and then the positive electrode active material was used to manufacture the positive electrode and rechargeable lithium battery cell in the same manner as in Example 1.

[0212] Comparative Example 3

[0213] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in essentially the same manner as in Comparative Example 2, except that in “(1) Preparation of positive electrode active material” in Comparative Example 2, a lithium-ion conductive solid electrolyte was included in an amount of 2% by weight based on the total weight of the positive electrode active material.

[0214] Comparative Example 4

[0215] The positive electrode active material was prepared in essentially the same manner as in Example 1, except that: in “(1) Preparation of the positive electrode active material” of Example 1, LiNi in the form of single particles with an average particle size of 3 μm manufactured by POSCO Holdings was used. 0.91 Co 0.08 Al 0.01 O2 is used as the core particle, and then the positive electrode and rechargeable lithium battery cell are manufactured in the same manner as in Example 1 using the positive electrode active material.

[0216] Evaluation Example 1: Analysis of the surface and coating of the positive electrode active material

[0217] Figures 5 to 9 This displays scanning electron microscope (SEM) images of the surfaces of the positive electrode active materials of Examples 2 and Comparative Examples 1 to 4, which are embodiments of this disclosure. Specifically, surface images of the positive electrode active materials of Examples 2 and Comparative Examples 1 to 4 were captured using a scanning electron microscope (SEM), and the results are shown below. Figures 5 to 9 middle.

[0218] It was confirmed that the positive electrode active material of Examples 2 and Comparative Examples 1 to 3 was in the form of secondary particles in which multiple primary particles agglomerated, while it was confirmed that the positive electrode active material of Comparative Example 4 was in the form of a single particle. At the same time, Comparative Example 2 did not have a relatively dark portion on the surface of the positive electrode active material, but the other examples and comparative examples each showed a relatively dark portion on the surface of the positive electrode active material, which confirmed the formation of a coating portion.

[0219] The surface of the positive electrode active material according to Example 2 was subjected to SEM-EDS (energy-dispersive X-ray spectroscopy) elemental mapping analysis, and the analysis results are shown in... Figure 10 and 11 middle.

[0220] Figure 10 and Figure 11 This displays the SEM-EDS analysis results of the surface of the positive electrode active material in Example 2, which embodies some embodiments of this disclosure. Carbon atoms are highlighted (highlighted) in the images. Figure 10 In this study, carbon (C) derived from the carbon-based material is uniformly distributed across the entire surface of the core particles, confirming that the carbon-based material is partially coated on the surface of the core particles as a continuous sheet or membrane. This is further demonstrated by the highlighting of phosphorus within the core particles. Figure 11 In the figure, P, which originates from the lithium-ion conductive solid electrolyte, is distributed on a portion of the core particle surface, confirming that the lithium-ion conductive solid electrolyte is coated on a portion of the core particle surface in the form of islands.

[0221] The number and thickness of graphene layers in the positive electrode active materials of Examples 1 and 2, and Comparative Examples 1, 3, and 4 were analyzed, and the results are shown in Table 1. The positive electrode active material of Comparative Example 2, which did not contain graphite particles, did not exhibit the formation of graphene with a layered structure and was therefore not evaluated. In the examples where evaluation was performed, the evaluation was specifically conducted by taking cross-sectional images of the positive electrode active material using a transmission electron microscope (TEM) to measure the thickness and number of layers at 20 points, and calculating the arithmetic mean of the measurement results.

[0222] Figures 12 to 16 Transmission electron microscopy images of the coating portions on cross-sections of the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1, 3 and 4, according to some embodiments of this disclosure, are shown. The thickness of the coating portions at various points is examined.

[0223] Table 1:

[0224]

[0225] Referring to Table 1, the coating portions of Examples 1 and 2 comprise graphene with a layered structure having 2 to 50 layers (particularly 20 layers or less), confirming that the coating portion comprising the graphene and the lithium-ion conductive solid electrolyte meets a thickness of about 1 nm to about 500 nm (or about 10 nm or less). (Refer to...) Figures 12 to 16 Confirmed Figure 12 Example 1 and Figure 13 Example 2 has a covering portion having a substantially uniform thickness. On the other hand, it has been confirmed that... Figure 14 Comparative Example 1 Figure 15 Comparative Example 3 and Figure 16 Comparative Example 4 has a relatively more uneven thickness of the coating portion compared to those in Examples 1 and 2.

[0226] Evaluation Example 2: Evaluation of Resistance

[0227] (1) Evaluation of powder resistance

[0228] The powder resistance of the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 to 4 was measured as follows: the pressure applied to the powder was controlled using a powder resistance meter equipped with a 4-pin probe (e.g., an instrument with the product name "RM3543" from the manufacturer Hioki EECorp.), and the results are shown in Table 2 below.

[0229] (2) Evaluation of interfacial resistance

[0230] The resistance formed at the electrode interface of the rechargeable lithium-ion coin half-cell cells of Examples 1 and 2 and Comparative Examples 1 to 4 was measured using an electrochemical impedance spectroscopy (EIS). The amplitude was set to ±10 mV, and the frequency was set in the range of 10 mHz to 1 MHz. The cell was charged at a constant current at a rate of 0.1 C to a maximum voltage of 4.25 V relative to the Li negative electrode, and then cut off at a current at a rate of 0.05 C while maintaining a constant voltage of 4.25 V. The cell was then allowed to stand for 1 hour to measure the resistance. Subsequently, the resistance was measured at the equilibrium voltage using an impedance analyzer according to the 2-probe method. The results are shown in Table 2, which show that the smaller the interface resistance of the cell, the easier the lithium-ion insertion and extraction during charging and discharging, and the more constant the charging and discharging efficiency. Therefore, the cell exhibits improved cycle life characteristics.

[0231] Evaluation Example 3: Performance Evaluation of a Rechargeable Lithium-ion Battery Cell

[0232] (1) Evaluation of initial charge / discharge capacity and efficiency

[0233] The initial charge / discharge capacity and efficiency of the rechargeable lithium-ion battery coin half-cells of Examples 1 and 2 and Comparative Examples 1 to 4 are evaluated as follows.

[0234] At room temperature (25°C), the battery cells were charged at a constant current of 0.2 C to an upper limit voltage of 4.45 V and then charged at a constant voltage to a rate of 0.05 C. The cells were then discharged at a rate of 0.2 C to a cutoff voltage of 3.0 V for initial charge and discharge. The efficiency was calculated according to Equation 1, and the results are shown in Table 2. Equation 1 is as follows:

[0235] [Equation 1]

[0236] Efficiency [%] = [Initial discharge capacity / Initial charge capacity] × 100.

[0237] (2) Evaluation of high temperature cycle life

[0238] The high-temperature cycle life of the rechargeable lithium-ion battery coin half-cells of Examples 1 and 2 and Comparative Examples 1 to 4 was evaluated.

[0239] After initial charging and discharging, the battery cells were repeatedly charged and discharged 50 times at a rate of 1.0 C within a voltage range of 3.0 V to 4.45 V at 45°C. The high-temperature cycle life was calculated according to Equation 2, and the results are shown in Table 2. Equation 2 is as follows:

[0240] [Equation 2]

[0241] High-temperature cycle life [%] = [Discharge capacity at 50th cycle / Discharge capacity at 1st cycle] × 100

[0242] Table 2:

[0243]

[0244] Referring to Table 2, it is confirmed that the positive electrode active materials of Examples 1 and 2 simultaneously satisfy a powder resistance greater than about 85 Ω·cm and less than about 150 Ω·cm and an interface resistance greater than or equal to about 50 Ω and less than about 150 Ω. In contrast, it is confirmed that the positive electrode active materials of Comparative Examples 1 to 4 do not satisfy at least one of the following: a powder resistance greater than about 85 Ω·cm and less than about 150 Ω·cm and an interface resistance greater than or equal to about 50 Ω and less than about 150 Ω.

[0245] Furthermore, compared to the rechargeable lithium battery cells of Comparative Examples 1 to 4, the rechargeable lithium battery cells of Examples 1 and 2 exhibited comparable or similar to or better initial charge capacity and initial charge / discharge efficiency, while also showing significantly improved initial discharge capacity and improved cycle life characteristics at high temperatures.

[0246] While some embodiments have been described above, this disclosure is not limited to the embodiments described above. Rather, this disclosure is also intended to cover various modifications and equivalent arrangements of the embodiments described above.

[0247] <Description of representative figure labels>

[0248] 100: Rechargeable lithium battery; 10: Positive electrode

[0249] 11: Positive electrode lead connector 12: Positive electrode terminal

[0250] 20: Negative electrode 21: Negative electrode lead connector

[0251] 22: Negative electrode terminal; 30: Diaphragm

[0252] 40: Electrode assembly; 50: Housing

[0253] 60: Seal 70: Electrode terminal

[0254] 71: Positive electrode connector; 72: Negative electrode connector

Claims

1. A positive electrode active material, comprising: a core in the form of secondary particles, the core comprising: a lithium nickel-based composite oxide; and a plurality of primary particles agglomerated with each other; and a coating portion disposed on a surface of the core, the coating portion comprising: graphene having a layered structure; and a lithium ion conductive solid electrolyte.

2. The positive electrode active material according to claim 1, wherein the layered structure comprises 2 to 50 layers.

3. The positive electrode active material according to claim 1, wherein the graphene of the coating portion is derived from graphite fine particles having an average dimension of less than or equal to 2.5 μm.

4. The positive electrode active material according to claim 3, wherein the graphite particles have a ratio of I ranging from 0.15 to 0.

50. D / I G The ratio I D / I G For the Raman spectrum at 1350 cm⁻¹ -1 Peak intensity I at D For 1580 cm -1 Peak intensity I at G .

5. The positive electrode active material according to claim 1, wherein the lithium ion conductive solid electrolyte is represented by the following formula: Li 1+x1 R x1 M 2-x1 (PO4)3, wherein R is a metal of Al, B, Sn, Ge or a combination thereof, wherein M is Ti, Zr, Hf or a combination thereof, and wherein 0≤x1<2.

6. The positive electrode active material according to claim 1, wherein the lithium ion conductive solid electrolyte is in the form of particles, and The average particle size D of the lithium-ion conductive solid electrolyte particles is described above. 50 The range is from 1 nm to 1 μm.

7. The positive electrode active material according to claim 1, wherein the positive electrode active material comprises the graphene in an amount of 0.01 wt% to 5 wt%, based on the total weight of the positive electrode active material.

8. The positive electrode active material according to claim 1, wherein the amount of the lithium ion conductive solid electrolyte is 0.05 wt% to 6 wt%, based on the total weight of the positive electrode active material.

9. The positive electrode active material according to claim 1, wherein the thickness of the coating portion is 1 nm to 500 nm.

10. The positive electrode active material according to claim 1, wherein the coating portion comprises: a first coating portion comprising the graphene; and a second coating portion comprising the lithium ion conductive solid electrolyte, wherein the first coating portion is in the form of a coating layer continuously surrounding the surface of the core, and wherein the second coating portion has a discontinuous island geometry on the surface of the core.

11. The positive electrode active material according to claim 1, wherein the positive electrode active material further comprises a grain boundary coating portion on a surface of the primary particles, the grain boundary coating portion comprising the lithium ion conductive solid electrolyte.

12. The positive electrode active material according to claim 1, wherein the lithium nickel-based composite oxide is represented by the following formula: Li a3 Ni x3 M 3 y3 M 4 z3 O 2-b3 X b3 , wherein 0.9≤a3≤1.2, 0.8≤x3<1, 0<y3≤0.2, 0≤z3≤0.2, 0.9≤x3+y3+z3≤1.1, and 0≤b3≤0.1, Where M 3 and M 4 Each is independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, Zr or combinations thereof, and wherein X is F, P, S or a combination thereof.

13. The positive electrode active material according to claim 1, wherein the nickel content of the lithium nickel-based composite oxide is greater than or equal to 80 mol%, based on 100 mol% of the total metals other than lithium in the lithium nickel-based composite oxide.

14. The positive electrode active material according to claim 1, wherein the average particle size D of the core is... 50 The thickness ranges from 8 μm to 20 μm.

15. The positive electrode active material according to claim 1, wherein the powder resistance of the positive electrode active material is greater than 85 Ω·cm and less than 150 Ω·cm.

16. A positive electrode, comprising: Positive electrode current collector; and A positive electrode active material layer is formed on the positive electrode current collector and includes the positive electrode active material according to any one of claims 1 to 15.

17. The positive electrode according to claim 16, wherein the interface resistance of the positive electrode is greater than or equal to 50 Ω and less than 150 Ω.

18. A rechargeable lithium battery, comprising: The positive electrode according to claim 16 or 17; negative electrode; and Electrolytes.